Infiltration patterns in monoclonal plasma cell disorders: correlation of magnetic resonance imaging with matched bone marrow histology - Andrulis, Mindaugas; Bäuerle, Tobias; Goldschmidt, Hartmut; Delorme, Stefan; Landgren, Ola; Schirmacher, Peter; Hillengass, Jens (European Journal of Radiology, 2014)
To investigate how plasma cell infiltration patterns detected by MRI match the plasma cell distribution in bone marrow biopsy.We assessed 50 patients with monoclonal plasma cell disorders of all clinical stages. MRI infiltration pattern was compared with matched BM histology from the same anatomic region.MRI revealed a minimal (n=11, 22%), focal (n=5, 10%), diffuse (n=14, 28%) and mixed (n=20, 40%) infiltration pattern. Diffuse MRI pattern was predominant in smoldering myeloma patients whereas the MRI patterns with "focal component" (i.e. focal and mixed) were most common in symptomatic myeloma (p<0.01). In histology an interstitial (n=13, 26%), nodular (n=23, 46%) and packed marrow (n=14, 28%) was found respectively. All three histological types of infiltration were observed in patients with diffuse and mixed MRI patterns. Minimal MRI pattern was found in all MGUS patients and was associated with an interstitial BM infiltration. In two patients with minimal MRI pattern an extensive micro-nodular BM infiltration was found in histology.Infiltration patterns in MRI represent different histological growth patterns of plasma cells, but the MRI resolution is not sufficient to visualize micro-nodular aggregates of plasma cells.
EVALuna2:14581